2020
DOI: 10.1002/jbm.a.37139
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a novel bovine cancellous bone/poly‐amino acid composite with low immunogenicity, proper strength, and cytocompatibility in vitro

Abstract: In this work, the delipidized and deproteinized bovine cancellous bone powder/poly–amino acid (DDBP/PAA) composite was fabricated by extrusion‐injection molding method for the first time. After about 70% clearance rate by the delipidization and deproteinization procedures, the residual antigens of galactosyl α–(1, 3)–galactosyl β–1,4–N–aeetylglueosaminyl (α–Gal) and major histocompatibility complex (MHC) II were basically eliminated by the extrusion–injection molding process, which may cause high titer of anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…It may lead to failure , Ca-O after implantation. Figure 6E showed the density of the obtained composites was about 1.3-1.5 g/cm 3 , which could match the density of cortical bone. Mechanical characteristic is critical in the selection of load-bearing bone materials.…”
Section: Mechanical Properties Of Paa/tha/tpva Compositesmentioning
confidence: 70%
See 1 more Smart Citation
“…It may lead to failure , Ca-O after implantation. Figure 6E showed the density of the obtained composites was about 1.3-1.5 g/cm 3 , which could match the density of cortical bone. Mechanical characteristic is critical in the selection of load-bearing bone materials.…”
Section: Mechanical Properties Of Paa/tha/tpva Compositesmentioning
confidence: 70%
“…Poly(amino acid) (PAA) is a synthetic polymer widely utilized in medical materials field due to its nontoxic degradation products and good biocompatibility. [ 3,4 ] However, the present PAA shows insufficient mechanical properties, which restricts its clinical application. [ 5 ] To solve these problems, combining bioactive minerals as fillers with the PAA matrix is a promising approach to compensate for the drawbacks of single material and obtain composites with extraordinary properties.…”
Section: Introductionmentioning
confidence: 99%
“…(DCBP/PAA EM) DCBP/PAA EM was fabricated by the method of EM (figure 1(B)). PAA was synthesized via melt polycondensation, according to our previous method [21]. The types and proportions of amino acids used were the same as those in section 2.2.1.…”
Section: Extrusion Molding (Em) Methodsmentioning
confidence: 99%
“…DCBP was prepared and characterized according to our previous publication [21]. Briefly, commercially available fresh bovine bones were used as raw materials and only fresh cancellous bones powder (FCBP) were retained.…”
Section: Preparation Of Delipidization Bovine Cancellous Bone Powdermentioning
confidence: 99%
“…The first critical criterion for preventing graft rejection is the examination of the remaining genomic material in ABGs. 71 Failure to remove genomic compounds not only leads to the rejection of rapid transplantation due to infection, but also due to the improper use of various drugs that suppress the immune system, it causes economic concerns and increases the invasion of foreign factors in other parts of the body. 72 It has been shown that reducing dsDNA below 50 ng/mg of ECM dry weight can guarantee very low immunogenicity of transplanted tissue.…”
Section: Abgs Function Evaluation Indicatorsmentioning
confidence: 99%